(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The article discusses the linguistic nature of phraseologisms in Uzbek fiction, the history of their formation, their place in the artistic text, the need for use, and the semantic and stylistic features of expressions. The article analyzes the comprehensive importance of phraseological units in creating the image of the hero and increasing the emotionality of the work, and talks about the issues of expressing the national color in the language.